Perfect plasticity of metals under simple shear: geometrical approach - Beygelzimer, Y.; Lavrinenko, N. (Физика и техника высоких давлений, 2012)
A mechanism of perfect plasticity is suggested that implies the phenomenon under study to be of ctitical nature. We consider that it is related to percolation transition in the net of grain boundaries and with nonlocal intraction of fragments uniquely under simple shear. Our point of view is substantiated by general reasoning, mainly of geometrical character, and also by employing computational modeling and well-known experimental results.